2017
DOI: 10.1093/bja/aex166
|View full text |Cite
|
Sign up to set email alerts
|

Predicting successful supraclavicular brachial plexus block using pulse oximeter perfusion index

Abstract: The PI is a useful tool for evaluation of successful supraclavicular nerve block. A PI ratio of > 1.4 is a good predictor for block success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
68
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(83 citation statements)
references
References 16 publications
5
68
3
Order By: Relevance
“…Full-field LDPI can evaluate and analyse perfusion but at low temporal resolutions. Pulse oximeter was reported to evaluate perfusion index after supraclavicular brachial plexus block 8 and sciatic nerve block. 9 However, this technology can only measure perfusion index on one digit and cannot provide the perfusion index at the ROIs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Full-field LDPI can evaluate and analyse perfusion but at low temporal resolutions. Pulse oximeter was reported to evaluate perfusion index after supraclavicular brachial plexus block 8 and sciatic nerve block. 9 However, this technology can only measure perfusion index on one digit and cannot provide the perfusion index at the ROIs.…”
Section: Discussionmentioning
confidence: 99%
“…3e5 LDPI can provide quantitative data on blood flow, but this technique is limited by poor temporal resolution. 6 Pulse oximeter technology was reported to predict the postspinal hypotension 7 and indicate block success for brachial plexus block 8 and sciatic nerve block. 9 Pulse oximeter measures changes in perfusion index, but one probe can only be placed on one digit within the same time period.…”
mentioning
confidence: 99%
“…Several methods have been described, such as measurement of peripheral flow index and perfusion index, both via pulse oximetry. Furthermore, an increase in electrical resistance of the skin has been identified as a reliable indicator of PNB, albeit questioned in later studies .…”
Section: Skin Temperature As An Indicator Of Regional Anaesthesia Sucmentioning
confidence: 99%
“…PI index was reported to change significantly at the fifth minute after a supraclavicular blockade. A. Abdelnasser et al reported that PI may be useful in determining the success of a supraclavicular blockade in patients undergoing orthopedic surgery [36]. Yamazaki et al [37].…”
Section: Discussionmentioning
confidence: 99%